Spatiotemporal Analysis of Potential Impact of Soil Erosion on Maize and Groundnuts Yield in Northern Ghana - Wilson Agyei Agyare; Eliasu Salifu (Journal of Applied Geospatial Information, 2021)
Abstract Soil erosion is a threat to the viability of arable land, which has a relationship with crop productivity. This study was carried out in the Northern, North-East and Savannah Regions of Ghana, which have a high agricultural potential. The study examined erosion-yield relationship by comparing estimated erosion rates with maize and groundnut yields in a GIS environment. The study also projected soil erosion and determined its potential effect on the yield of maize and groundnuts. The soil erosion rates were found to be 4.2 t ha-1y-1, 5.1 t ha-1y-1 and 7.1 t ha-1y-1 for the Northern, North-East and Savannah Regions respectively. Projections for the next 10 years showed that, soil erosion will averagely increase by about 12 %, which could reduce the yield of maize and groundnut by 21 % and 16 % respectively by the year 2031, should the current trend continue. The study also found out that crop (maize and groundnut) yield per land area is relatively lower in areas severely affected by soil erosion. Farmers in the study area and areas of similar ecology must be encouraged to adopt Soil and Water Conservation (SWC) strategies to enhance and sustain productivity.